Utilization of posters as educational media on balanced nutrition at SD Negeri Citapen Tasikmalaya - Ghaitsa Zahira Arya; Dedi Purwanto (Universitas Pendidikan Indonesia, 2023)
KKN is one of the community service activities and implementation of the Tri Dharma of Higher Education. Thematic KKN (KKNT) carried out by the Indonesian Education University carries the theme Si Penting (Mahasiswa Peduli Stunting). This problem is in line with the World Health Organization (WHO) priority to reduce stunting globally. Stunting is a growth obstacle resulting from a lack of nutritional intake in children. To prevent children from experiencing stunting problems, they need to get used to healthy living. The approach taken is through poster educational media to strengthen the material implemented at SD Negeri Citapen Tasikmalaya City, so that the entire school community receives information related to balanced nutrition. The steps in the KKNT program start from the preparation stage to the activity implementation stage. Posters are considered to be an appropriate medium because they contain interesting images and symbols so that information is more easily conveyed. It is hoped that the poster educational media creation program will have the opportunity to become a media for literacy and familiarization regarding the importance of consuming balanced nutrition through guidelines on the contents of my plate, drinking at least 8 glasses of water a day, washing hands properly and correctly using the 6 steps from the Ministry of Health, and diligently exercising for at least 30 minutes a day. Abstrak Kuliah Kerja Nyata (KKN) merupakan salah satu kegiatan pengabdian kepada masyarakat dan pengimplementasian Tri Dharma Perguruan Tinggi. KKN Tematik (KKNT) yang dilaksanakan oleh Universitas Pendidikan Indonesia membawakan tema “Si Penting (Mahasiswa Peduli Stunting)”. Permasalahan ini sejalah dengan prioritas World Health Organization (WHO) untuk mengurangi stunting secara global. Stunting merupakan hambatan pertumbuhan yang diakibatkan dari kurangnya asupan gizi yang terjadi pada anak. Untuk menghindari anak dari permasalahan stunting diperlukan pembiasaan untuk hidup sehat. Pendekatan yang dilakukan adalah melalui media edukasi poster untuk penguatan materi yang dilaksanakan di SD Negeri Citapen Kota Tasikmalaya, agar seluruh civitas sekolah mendapatkan informasi terkait gizi seimbang. Langkah-langkah dalam program KKNT ini dimulai dari tahap persiapan hingga tahap pelaksanaan kegiatan. Poster dirasa menjadi media yang sesuai dikarenakan berisikan gambar dan simbol yang menarik sehingga informasi lebih mudah tersampaikan. Program pembuatan media edukasi poster diharapkan berpeluang sebagai media literasi dan pembiasaan terkait pentingnya mengonsumsi gizi seimbang melalui pedoman isi piringku, meminum air minimal 8 gelas sehari, melakukan cuci tangan yang baik dan benar dengan 6 langkah dari Kementrian Kesehatan, serta rajin berolahraga minimal 30 menit sehari. Kata Kunci: gizi seimbang; media edukasi; poster; SD Negeri Citapen; stunting